Neuroprotective Effect of Visnagin on Kainic Acid-induced Neuronal Cell Death in the Mice Hippocampus - Kwon, Min-Soo (The Korean Physiological Society and The Korean Society of Pharmacology, 2010)
Visnagin (4-methoxy-7-methyl-5H-furo[3,2-g][1]-benzopyran-5-one), which is an active principle extracted from the fruits of Ammi visnaga, has been used as a treatment for low blood-pressure and blocked blood vessel contraction by inhibition of calcium influx into blood cells. However, the neuroprotective effect of visnagin was not clearly known until now. Thus, we investigated whether visnagin has a neuroprotective effect against kainic acid (KA)-induced neuronal cell death. In the cresyl violet staining, pre-treatment or post-treatment visnagin (100 mg/kg, p.o. or i.p.) showed a neuroprotective effect on KA (0.1 µg) toxicity. KA-induced gliosis and proinflammatory marker (IL-1β, TNF-α, IL-6, and COX-2) inductions were also suppressed by visnagin administration. These results suggest that visnagin has a neuroprotective effect in terms of suppressing KA-induced pathogenesis in the brain, and that these neuroprotective effects are associated with its anti-inflammatory effects.